New insights into the phylogeographic distribution of the 3FTx/PLA2 venom dichotomy across genus Micrurus in South America - Sanz, Libia (2019)
Micrurus is a monophyletic genus of venomous coral snakes of the family Elapidae. The ~80 recognized species within this genus are endemic to the Americas, and are distributed from southeastern United States to northern Argentina. Although relatively few bites are recorded due to their reclusive nature, semi-fossorial habits, and their occurrence in sparsely populated areas, coral snakes possess powerful venoms that target the cholinergic system and, if early treatment is missed, can cause neuromuscular paralysis, respiratory failure, and death by asphyxiation within hours of envenoming. The to-date proteomically characterized 18 micrurine venoms exhibit a puzzling phenotypic dichotomy, characterized by the toxin arsenal being dominated either by pre-synaptically acting PLA2s or post-synaptic 3FTxs, and a general, but imperfect, distributional pattern of these venom phenotypes along the North-South axis of the American continent. The lack of perfect phylogenetic clustering suggests that phylogeny may not be the sole factor driving the evolution of the divergent venom phenotypes across Micrurus venoms. To shed new light on the origin and expression pattern of the 3FTx/PLA2 venom dichotomy, we have conducted a comparative proteomics analysis of venoms from the Brazilian ribbon coral snake, Micrurus lemniscatus carvalhoi, sourced from different localities in the Brazilian states of São Paulo; the Caatinga coral snake, M. ibiboboca, from central Bahia state (Brazil); two Micrurus specimens of uncertain taxonomy collected in the Brazilian states of Alagoas and Rio de Janeiro; and the Western ribbon coral snake, M. l. helleri, from Leticia, the southernmost town of the Colombian Department of Amazonas. Venoms from São Paulo and Rio de Janeiro showed 3FTx-predominant phenotypes, while in venoms from Leticia, Alagoas and Bahia PLA2s represented the major toxin family. Comparative venom proteomics suggests that both Micrurus venom phenotypes exhibit a high degree of toxin evolvability. Mapping the 3FTx/PLA2 dichotomy across the Americas points to a phylogeographic pattern for venom phenotypes consistent with, but more complex than, the North-South distribution hypothesis anticipated in previous investigations. Biological significance: New World coral snakes (Micrurus: Elapidae) produce potent venoms that target pre- and post-synaptically cholinergic nerve terminals resulting in neuromuscular paralysis, and in severe envenomings, may lead to death from asphyxiation by respiratory arrest. Presynaptic β-neurotoxins of group IA PLA2 protein subfamily and postsynaptic α-neurotoxins with 3FTx fold are the major components (> 80%) of coral snake venoms. Micrurine venoms exhibit a puzzling phenotypic venom dichotomy, characterized by the dominant expression of either α- or β-neurotoxins. The distribution of these alternative compositional profiles has been fragmentarily studied both across Micrurus phylogeny and along the North-South axis of the genus radiation in the American continent, from southern United States to Northern Argentina. The unpredictability of the neurotoxin profile across the distribution range of the coral snakes represents a difficulty for applying the most appropriate treatment upon a coral snakebite. A deep knowledge of the phylogeographic distribution and the evolution of dichotomic Micrurus venoms would be useful for tracing the evolutionary path to their present day phenotypes, rationalizing the patchy cross-reactivity of current Micrurus antivenoms, and improving the efficacy of antivenoms to neutralize coral snake envenomings.